Discovery of Chemicals to Either Clear or Indicate Amyloid Aggregates by Targeting Memory‐Impairing Anti‐Parallel Aβ Dimers. (7th May 2020) - Lee, Jinny Claire; Kim, Hye Yun; Lee, Sejin; Shin, Jisu; Kim, Hyunjin Vincent; Kim, Kyeonghwan; Baek, Seungyeop; Lee, Donghee; Jeon, Hanna; Kim, DaWon; Yang, Seung‐Hoon; Han, Gyoonhee; et al.
Abstract: Amyloid‐β (Aβ) oligomers are implicated in Alzheimer disease (AD). However, their unstable nature and heterogeneous state disrupts elucidation of their explicit role in AD progression, impeding the development of tools targeting soluble Aβ oligomers. Herein parallel and anti‐parallel variants of Aβ(1–40) dimers were designed and synthesized, and their pathogenic properties in AD models characterized. Anti‐parallel dimers induced cognitive impairments with increased amyloidogenesis and cytotoxicity, and this dimer was then used in a screening platform. Through screening, two FDA‐approved drugs, Oxytetracycline and Sunitinib, were identified to dissociate Aβ oligomers and plaques to monomers in 5XFAD transgenic mice. In addition, fluorescent Astrophloxine was shown to detect aggregated Aβ in brain tissue and cerebrospinal fluid samples of AD mice. This screening platform provides a stable and homogeneous environment for observing Aβ interactions with dimer‐specific molecules. Abstract : On target : Parallel and anti‐parallel amyloid‐β (Aβ) homodimers were fabricated and screened, and the anti‐parallel dimers induced cognitive impairment with increased amyloidogenesis and cytotoxicity. In vitro/vivo assessments of the drugs Oxytetracycline and Sunitinib show that they target Aβ dimers and larger aggregates, thus identifying therapeutic and diagnostic agents for Alzheimer disease.